ANALISIS IMPLEMENTASI KEBIJAKAN PADA RANTAI PASOK PRODUK PERTANIAN - Shoffiyati, Peni; Noer, Melinda; Z, Rahmat Syahni; Asrinaldi (Agripita Publisher, 2017)
Supply chain management is the management of the entire process of production, distribution and marketing to allow consumers to supply the desired product. To ensure the basic needs of the national supply chain, the government issued a policy in the form of Presidential Regulation Number 71 Year 2015 concerning the Stipulation and Storage Basic Foodstuffs and Essential Goods. Staples in this policy is the stuff that concerns the lives of many people with high scale of perceived needs and be a factor supporting the welfare of society, in this case including staples result / agricultural products. Agricultural commodity supply chain policy is a form of government control of the availability of supplies and stability of agricultural commodity prices. This paper analyzes the policy-setting and storage of agricultural products in order to protect the perpetrators of the supply chain from upstream to downstream. On the policy of price stability, the reference price is an effort to protect consumers and farmers. The problem that occurs is the traders who do not follow the reference price set by the government on farm products that include such basic needs. While the policy of stock management and logistics, the government guarantees the availability of supplies. In practice some agricultural product supply chain actors more interested in selling their products outside the region attracted by the higher prices. The weakness of existing policies so far is more focused on the technical implementation of supply management.